Modification of impurity transport in the presence of saturated (m, n) = (1, 1) MHD activity at ASDEX Upgrade. (20th May 2015) - Sertoli, M; Dux, R; Pütterich, T
Abstract: Impurity transport in sawtoothing plasmas in the presence of long lived inter-crash MHD activity is analysed in an ASDEX Upgrade discharge. In order to describe the time-evolution of the soft x-ray (SXR) time-traces after argon trace impurity injection, two sets of transport coefficients, switching at the onset of the mode, are necessary. The non-linear time evolution of the background SXR emissivity leads on the other hand to systematic errors that cannot be eliminated from the transport analysis. Typical experimental methods for the determination of the transport coefficients are demonstrated to be inapplicable and a way to determine the intrinsic density form a combination of SXR and vaccum-ultraviolet measurements is explained. Ideas for new ways to probe impurity transport in two dimensions in the presence of long-lived MHD activity are given.